Tax Incentives Pathfinder under COVID-19 - Pangestuti, Dinik Fitri Rahajeng; Zahiroh, Mun Yah (Universitas Ahmad Dahlan, 2024)
This research aims to comprehensively analyze the implementation of tax incentive strategies in mitigating the economic impact of COVID-19, grounded in endogenous growth theory. Utilizing a literature review of 134 articles published between 2020 and 2023, this study evaluates tax incentives as public policy interventions, comparing practices globally to provide insights for Indonesia. The Population, Intervention, Comparison, Outcomes, and Context (PICOC) framework is employed to ensure the validity and reliability of the literature, while Publish or Perish citation metrics assess the quality of sources. Findings indicate that tax incentives strategically counter economic downturns by boosting purchasing power, sustaining businesses, and improving compliance. However, their effectiveness could be enhanced due to a lack of taxpayer awareness. To address this, the study recommends developing more comprehensive, interactive, and measurable socialization programs alongside strengthening the role of Account Representatives in assisting taxpayers. This research contributes to the existing literature by providing a detailed review of tax incentive policies implemented during the pandemic, focusing on Indonesia and comparisons with other Southeast Asian countries. The study aims to offer insights into best practices for designing and implementing tax incentives, particularly in crises, to better align these policies with sustainable economic growth.